Immunological and Clinical Effect of Diet Modulation of the Gut Microbiome in Multiple Sclerosis Patients: A Pilot Study - Saresella, Marina; Mendozzi, Laura; Rossi, Valentina; Mazzali, Franca; Piancone, Federica; LaRosa, Francesca; Marventano, Ivana; Caputo, Domenico; Felis, Giovanna E.; Clerici, Mario (Frontiers in Immunology, 2017)
Pathogenesis of autoimmune disorders, including Multiple Sclerosis (MS), has been linked to an alteration of the resident microbial commensal community and of the interplay between the microbiota and the immune system. Dietary components such as fibers, acting on microbiota composition, could, in principle, result in immune modulation and, thus, could be used to obtain beneficial outcomes for patients. We verified this hypothesis in a pilot study involving two groups of clinically similar Relapsing-Remitting (RR) MS patients who had undergone either a high-vegetable/low-protein diet (HV/LP diet group; N=10) or a standard western diet (WD group; N=10) for at least 12 months. Gut microbiota composition, analyzed by 16S V4 rRNA gene sequencing and immunological profiles, were examined after a minimum of 12 months of diet. Results showed that, in the HV/LP diet group compared to the WD group: 1) Lachnospiraceae family was significantly more abundant; 2) IL-17-producing T CD4+ lymphocytes (p= 0.04) and PD-1 expressing T CD4+ lymphocytes (p= 0.0004) were significantly decreased; and 3) PD-L1 expressing monocytes (p= 0.009) were significantly increased. In the HV/LP diet group, positive correlations between Lachnospiraceae and both CD14+/IL-10+ and CD14+/TGFbeta+ monocytes (RSp=0.707, p=0.05 and RSp= 0.73, p=0.04; respectively), as well as between Lachnospiraceae and CD4+/CD25+/FoxP3 T lymphocytes (RSp= 0.68,p=0.02) were observed. Evaluation of clinical parameters showed that in the HV/LP diet group alone the relapse rate during the 12 months follow up period and the EDSS score at the end of the study period were significantly reduced.. Diet modulates dysbiosis and improves clinical parameters in MS patients by increasing anti-inflammatory circuits. Because Lachnospiraceae favour Treg differentiation as well as TGFbeta and IL-10 production this effect could be associated with an increase of these bacteria in the microbiota.